Uma investigação de aspectos psicodinâmicos da transexualidade por meio da Terapia Breve de Sandplay - Khouri, Julia Kaddis El (2020)
This research was based on Jungian analytical psychology and derived from clinical experience and observations regarding the suffering experienced by transsexual persons who reported that they suffered from feelings of incongruence between their gender identity and their biological sex. The research was carried out with three participants and discussed the possibility of comprehending and reframing these conflicts using Brief Sandplay therapy (BST), an expressive and experiential method, structured within a limit of sessions, may enables latent emotions and conflicts to be expressed, favoring the reorganization of the internal world and development of the personality. Thus, the objectives of this research were: (1) observe the benefits of BST in the improvement of clinical or limitrophe symptoms, related to internalizing and/or externalizing factors based on the inventory for the ASR (Adult Self-Report) /ASEBA; (2) observe any changes in the rating for the World Health Organization Quality of Life Assessment (WHOQOLBref) after BST; (3) undertake a psychodynamic analysis adopting a Jungian approach, based on three case studies, and (4) observe the data collected from the interviews, at the beginning and at the end of the process, in order to access meanings given by the participants regarding the feelings of incongruity between their gender identity and their biological sex, after TBS. A qualitative approach was adopted for this research, based on case studies. The results of the ASR (Adult Self-Report)/ASEBA showed an improvement in the rating for clinical or limitrophe symptoms in relation to the internalizing and/or externalizing factors for the three cases analyzed, even when the rating did not remain stable in the subsequent months, until the follow-up evaluation. The results of the WHOQOL-Bref, in most of its domains, also reported changes in the ratings and the replies to the interview, after BST, reported changes in the way the participants began to reframe the feeling of incongruence. The psychodynamic analysis of the therapeutic process, based on the three case studies, had partial results, being a temporary cut in the context and moment of transition in the participants’ transsexualizing process and due to the technique used. However, within the limits of a brief therapy, the research participants found in BST, support and continence for the feeling of incongruity between their gender identity and their biological sex and were able to reframe their values and choices, strengthening the personality in order to face the challenges and resistance of a society still based on old paradigms